Improving Insurance Penetration in the Under-Developed Area with the Instrumentality of Third-Party Agents - Saka; Toyin, Shafau; Abere (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
This study examined the potential use of third-party agencies as a means of reaching low-income rural earners with insurance offers and services. The people living in the Ikorodu neighborhood received attention. Respondents were asked to complete a questionnaire, and the information was then analyzed using the Logit Binary Regression Model. According to the report, the most mitigating factors preventing the expansion of insurance services among people living in rural areas are poverty and illiteracy. This study came to the conclusion that marketing small goods insurance (such as phones, televisions, etc.) and third-party agents through the operation of insurance point of sale stands should be done in order to promote, develop, and increase insurance in rural areas.